THE PHENOMENON OF "AA PITY AA" IN THE PERSPECTIVE OF THE QUR'AN (STUDY OF AL-AZHAR TAFSIR ON THE VERSE OF ASKING) - Nur Faizah; Tutik Hamidah (Journal of Learning on History and Social Sciences, 2024)
This study aims to explore the phenomenon of begging in the social and economic context of Indonesia, focusing on the factors that influence the practice of begging, community responses, and solutions that can eradicate it. The research method used is qualitative with a descriptive approach, using data collection techniques through literature studies, observations, and in-depth interviews. Literature studies are used to gain a deep theoretical understanding of the phenomenon of begging, economic empowerment, and related religious values. Observations are conducted to observe direct interactions between beggars and the community, while in-depth interviews are conducted with relevant respondents such as beggars, religious figures, social activists, and policy experts. The results of the study indicate that the phenomenon of begging is influenced by complex factors such as low levels of education, minimal job opportunities, and community attitudes toward beggars. Community responses to beggars vary from empathy to ambivalence, with the perception that begging is not an effective long-term solution. In the context of religious values, the practice of begging is regulated within the framework of allowing begging in emergencies, but strongly encouraging independence and economic productivity through zakat, alms, and economic empowerment. The implication of this study is the need for an integrated approach from various sectors of society, including religion, social, and economic, in formulating more effective and sustainable policies to reduce the phenomenon of begging. Further research is suggested to expand the scope of the study, integrate cross-disciplinary approaches, and further evaluate economic empowerment programs that can change the paradigm of beggars towards a more independent and sufficient life